3D projection mapping for facial cosmetic surgery by creating a 3D video - Vasudevan, Vani (International Journal of Engineering and Technology, 2018)
Due to the rapid growth of technology, millions of systems are designed day by day to fulfill their duties in facilitating the human lives. In this paper, the projection mapping method is used to help users who need to do facial cosmetic surgery in taking the right decisions by providing them with a unique system, which can be used in cosmetic surgeries’ clinics. The main purpose of the system is to make a projection mapping on a face model that presents the changes that need to be applied on the face features with some facial expressions, as a result, the user will be able to compare between his/her face before and after the surgery and take the certainly decision. A suitable web based UI is created to make it easier for the user by enabling him/her to choose the needed surgery and come up with his/her own projection mapping video.